Sensory, physicochemical and rheological properties of plant‐based milk alternatives made from soybean, peanut, adlay, adzuki bean, oat and buckwheat. (12th June 2022) - Yao, Yueying; He, Wenmeng; Cai, Xifan; Bekhit, Alaa El‐Din Ahmed; Xu, Baojun
Summary: This study investigated the physicochemical and sensory properties of six types of plant‐based milk alternatives prepared from soybean, peanut, adlay, adzuki bean, oat and buckwheat at a 1:9 grain‐to‐water ratio. The results revealed that all plant‐based milk types had stable hydrocolloid systems, except for the buckwheat milk alternative that had undergone a gelatinisation process that affected its rheological and sensory properties. The pH values and total solid content of the prepared plant‐based milk samples ranged between 6.60 to 6.83 and 2.13 to 8.17 g/100 mL, respectively. The sensory results showed that the overall liking score of adlay, adzuki bean and peanut milk alternative was 5.32, 5.30 and 6.10, respectively, suggesting a potential for commercial production. In conclusion, this investigation provides new insights on several new plant sources for plant‐based milk alternatives. Further studies are required to investigate the digestibility and the nutritional effects expected from plant‐based milk alternatives such as protein bioavailability, and the effects on human health compared to other animal milks. Abstract : The experimental process.